Tax Avoidance in Islamic Banking: The Prominent Role of Board Director Expertise - Fitriana, Vita Elisa; Soleha, Salwa Sabila; Mapuasari, Supeni Anggraeni (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2023)
This study examines the effect of board director expertise, political connection, and joint audit on tax avoidance. Specifically, a joint audit is the moderating variable in that relationship. This study uses a purposive sampling method where the sample was generated from the Islamic banking industry from 2012 to 2021 with 11 companies. Further, the data was analyzed using the multiple regression method. The results showed that board director expertise could boost the company's tax avoidance practice. The high understanding of directors on accounting, particularly tax regulations, enhances their possibility of using the regulations’ loopholes to decrease the company’s payable tax. This result is highly supported by upper echelon theory, which postulates that the ability of the top management level (i.e., board of director) is created by their experience, value, and personality. Hence, their expertise is sufficient to influence tax avoidance. On the other hand, the remaining variables tested did not show a significant effect. This result highlighted the importance of the company’s consideration in choosing their expertise. Again, the board director's expertise is the most prominent factor instead of political connection and joint audit on tax avoidance.